1990
DOI: 10.1017/s0003356100012514
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dam and sire group on the propensity for twin calving in cattle

Abstract: Link to this article: http://journals.cambridge.org/abstract_S0003356100012514How to cite this article: C. A. Morris and A. M. Day (1990). Effects of dam and sire group on the propensity for twin calving in cattle. ABSTRACTThe incidence of twin calvings and double ovulations was studied in two Milking Shorthorn herds and one Friesian herd, each with above-average annual twin calving rates (average 0-031, compared with a national rate of 0-01). The proportions of double ovulations were calculated from records c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

1991
1991
2012
2012

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 6 publications
1
9
0
1
Order By: Relevance
“…This was consistent with our preliminary findings from two herd years (Morris & Day 1987), but in contrast to resultsfromthe smallercomparison by Labhsetwar et al (1963),whereno relationship was found.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This was consistent with our preliminary findings from two herd years (Morris & Day 1987), but in contrast to resultsfromthe smallercomparison by Labhsetwar et al (1963),whereno relationship was found.…”
Section: Discussionsupporting
confidence: 92%
“…Inter-calving intervals in the United States 405 of Americawere reportedas 399, 387, and 398 days (Dunbar & Henderson 1953;Everett et al 1966;Nieuwhof et al 1989) compared with 365 days in New Zealand (Macmillan & Moller 1977). Thus, American Holsteins may have higher twin calving rates than New Zealand Friesians (see review by Morris & Day 1986), partly because of the 4-week difference in CCI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This had the effect of roughly halving the true numbers of cows calving per year, and the true numbers of calvings per cow lifetime, but with minimal bias on the genetics of calving singles or twins. We have examined means for TCR, BLT, and NLT from Herds A-C previously, up to their 1987 calvings (Morris & Day 1990), and have now included up to 13 more calving years. Previously, we found evidence of sire and dam genetic effects with no significant interaction, indicating that twinningeffects from both parents could be selected for (or against), although the heritabilities were not estimated at that time.…”
Section: Data Collection From Private Herdsmentioning
confidence: 99%
“…It was noticeable that second and third twin calvings contributed to the apparently higher TCR in the (T x T) line in calving years 1995-1997 and 1998-2000, mainly from the five families. Earlier analyses of twin calvings from selected private herds (Morris & Day 1990) identified that elite daughters (sired by elite bulls and out of elite dams) had a mean BLT of 39%. Two of the research-herd families in Table 4, comprising 19 cows, had a mean BLT greater than this, suggesting that they are perhaps candidates for further intense study.…”
Section: Research Herd Averagesmentioning
confidence: 99%